International Business and Multinational Enterprises / Fourth Edition - Robock H. Stefan; Simmonds Kenneth (Irwin Mcgraw-Hill, 1989)
The Nature and Scope of International Business, The Framework for International Transactions, Global Business Strategy, The Nation-State and International Business, Multinational Operations Management, Emerging Issues, Cases and Problems in International Business, Author and Subject Index.